Development of a Berry Processing Score for Sorghum Silage and Assessment of Processing Effects on Sorghum Silage Starch Digestibility - J. R. Johnson; J. P. Goeser; Michael Brouk (Kansas Agricultural Experiment Station Research Reports, 2017)
The objectives of this study were to develop a berry processing score (BPS) for sorghum silage, similar to the kernel processing score currently used for corn silage, and to evaluate the effects of processing on starch digestibility. Sorghum silage samples were collected from commercial farms in Kansas and randomly assigned to 1 of 4 processing levels differing in roll gap spacing: unprocessed (UNP), 1.5 (1.5P), 1.0 (1.0P), or 0.5 (0.5P) mm. Differences in BPS and starch digestibility were found–as the roll gap decreased, both BPS and starch digestibility increased. Thus, by processing sorghum silage during harvest and measuring the extent of processing, sorghum silage starch digestibility can be greatly enhanced. Sorghum silage may serve as a viable alternative to corn silage in the diets of lactating dairy cows in areas of the country where corn silage is a high-risk forage crop due to lack of water.
Keywords: sorghum silage; processing; starch digestion